2000
DOI: 10.1063/1.371997
|View full text |Cite
|
Sign up to set email alerts
|

Properties of nanoporous silica thin films determined by high-resolution x-ray reflectivity and small-angle neutron scattering

Abstract: A new methodology based on a novel combination of a high-resolution specular x-ray reflectivity and small-angle neutron scattering has been developed to evaluate the structural properties of low-dielectric-constant porous silica thin films about one micrometer thick supported on silicon wafer substrates. To complement these results, film composition was determined by high-energy ion scattering techniques. For the example thin film presented here, the overall film density was found to be (0.55Ϯ0.01) g/cm 3 with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(51 citation statements)
references
References 13 publications
(15 reference statements)
0
51
0
Order By: Relevance
“…194 Reflection attenuation IR also allowed to observe S2R sites. 142 SiO x films on silicon can grow up to at least 1 micrometer thick while still allowing the use of surface techniques such as specular x-ray reflectivity and SANS (small-angle neutron scattering), 195 and this would be expected to remove the structural influence of the substrate.…”
Section: Iras Stm Leed: « Flat » Silica Surfacesmentioning
confidence: 99%
“…194 Reflection attenuation IR also allowed to observe S2R sites. 142 SiO x films on silicon can grow up to at least 1 micrometer thick while still allowing the use of surface techniques such as specular x-ray reflectivity and SANS (small-angle neutron scattering), 195 and this would be expected to remove the structural influence of the substrate.…”
Section: Iras Stm Leed: « Flat » Silica Surfacesmentioning
confidence: 99%
“…If this is not known a priori (as is the case here), a combination of forward recoil elastic scattering and Rutherford backscattering can be used to measure the film atomic composition, as described previously. 2,3 Table 1 summarizes the atomic composition for the three films reported in this work. 11 If the film is not swollen by toluene, then the electron density determined from the critical edges of the dry and the toluene-infiltrated films can be used to calculate the mass uptake of toluene.…”
Section: Resultsmentioning
confidence: 99%
“…For example, we have shown that a combination of neutron scattering, ion-beam scattering, and X-ray reflectivity experiments can elucidate detailed pore information, such as porosity and the average pore size. 2,3 The applicability of this methodology is, however, limited because neutron scattering is not a laboratory-scale facility. Attractive alternatives for measuring pore sizes in thin films include the positron beam techniques (lifetime spectroscopy and Doppler broadening measurements) that are especially useful for characterizing the very smallest pores (i.e., 2-20 Å in diameter).…”
Section: Introductionmentioning
confidence: 99%
“…An increasingly method is to extend a low-resistivity and lowk dielectric materials allowing the contact to overlap onto, or be completely on the field oxide as shown in the following Figure 1. Hence, we had carried out the analysis of various structural and electrical parameters such as the parasitic capacitance, crosstalk, and line signal [17,18]. The paper has four sections; the following section two describes the brief experimental process, while section three has been dedicated for the results and discussion finally in section four we presented the concluding remarks.…”
Section: Introductionmentioning
confidence: 99%